2022
DOI: 10.18637/jss.v102.i10
|View full text |Cite
|
Sign up to set email alerts
|

More on Multidimensional Scaling and Unfolding in R: smacof Version 2

Abstract: The smacof package offers a comprehensive implementation of multidimensional scaling (MDS) techniques in R. Since its first publication (De Leeuw and Mair 2009b) the functionality of the package has been enhanced, and several additional methods, features and utilities were added. Major updates include a complete re-implementation of multidimensional unfolding allowing for monotone dissimilarity transformations, including row-conditional, circular, and external unfolding. Additionally, the constrained MDS imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 55 publications
0
35
0
3
Order By: Relevance
“…Finally, we conducted a multidimensional scaling analysis of the raw data of text-based scores, using the smacof package (Mair et al, 2021 ). We specified ordinal data structure and plotted two dimensions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we conducted a multidimensional scaling analysis of the raw data of text-based scores, using the smacof package (Mair et al, 2021 ). We specified ordinal data structure and plotted two dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…Achievement, Stimulation and Hedonism values had reliabilities below 0.70 [for a discussion of reliability issues with this measure, refer to Schwartz and Cieciuch ( 2021 )]. To examine the theoretical structure, we conducted a multidimensional scaling analysis with the smacof package (Mair et al, 2021 ) and Euclidean distances based on Pearson's correlations, ordinal data structure, and extracting two dimensions. Compared to the theory-predicted positions (Bilsky et al, 2011 ), our data showed acceptable conceptual similarity (congruence = 0.88) in line with minimum standards for conceptual replication (Fischer and Fontaine, 2011 ; Fischer and Karl, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, Biplot analysis provides a structure of diversity in MDS where data involves variables and not just dissimilarities [31]. In this way, Biplot analysis allows mapping the external variables on MDS configuration, and establishing validation for variables on dimension [32].…”
Section: Multidimensional Scalingmentioning
confidence: 99%
“…The penalized stress function is minimized through numerical optimization using a strategy called SMACOF (Stress Majorization of a Complicated Function) and is implemented in an R package of the same name (de Leeuw & Mair, 2009). For details on multidimensional unfolding and its implementation see Mair et al (2021), Borg and Groenen (2005), and Busing et al (2005).…”
Section: Multidimensional Unfoldingmentioning
confidence: 99%